The Effect of Destination Brand Awareness on Destination Brand Loyalty Through Brand Image, Perceived Brand Quality, Brand Value and Brand Satisfaction in Banyuwangi City As a Tourism Objective - Heri Subagyo (Archives of Business Research, 2019)
This research is about the Influence of Destination Brand Awareness on Destination Brand Loyalty Through Brand Image, Perceived Brand Quality, Brand Value and Brand Satisfaction in Banyuwangi City as a Tourism Destination. The study population was tourists visiting Banyuwangi City in East Java from March to May 2018. Using SEM rules, the sample size was 250 respondents. Test models with Generalized Least Square Estimation (GLS), structural equation model analysis (SEM), Purposive sampling method in incidental sampling and assistance with Amos 24 software, on 250 respondents. The test results show the model (fit) seen from the values ​​of GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF, respectively at 0.916, 0.902, 0.951, 0.954, 0.074 and 0.977 all of which are within the range of expected values ​​so that the model can be accepted. The results of the study show that: 1). Destination brand awareness affects the destination brand image. 2). Decination of brand awareness has an effect on destination brand value. 3). Destination brand image has no significant effect on destination brand quality. 4). Destination brand image affects destination brand value. 5). Destination brand image influences destination brand loyalty. 6). Destination brand quality affects destination brand value. 7). Destination brand quality affects destination brand loyalty. 8). Destination brand value influences destination brand satisfaction. 9). Destination brand value affects destination brand loyalty. 10). Destination brand satisfaction affects destination brand loyalty.